Polymyxin B Induced Facial Rash and Superficial Thrombophlebitis: A Dual Adverse Drug Reaction - Dawaiwala, Idris; Bhagat, Soniya; Zirpe, Kapil; Shah, Aniket; Deshmukh, Abhijeet; Muglikar, Prasad (Indian Journal of Pharmacy Practice)
Polymyxin B is a last-line therapy for multidrug-resistant Gram-negative infections, with nephrotoxicity and neurotoxicity being the most recognized adverse effects. Cutaneous and vascular complications are rare and underreported. We describe a 34-year-old male with carcinoma of the buccal mucosa who developed surgical site infection due to MDR Klebsiella pneumoniae. He received intravenous polymyxin B (0.75 million units per dose, twice daily, as per institutional ICU protocol), and on Day 4 developed a non-pruritic facial maculopapular rash and infusion-site pain with Doppler-confirmed superficial thrombophlebitis. Both resolved after drug withdrawal and supportive management. Causality assessment using Naranjo and WHO-UMC scales indicated a probable association. To our knowledge, this is the first Indian report of simultaneous dermatologic and vascular adverse reactions to polymyxin B. Early recognition and preference for central venous access may prevent complications and improve safety.
Keywords: Adverse drug reaction; Drug-induced rash; MDR Klebsiella; Polymyxin B; Thrombophlebitis